Pengaruh Green Accounting, Ukuran Perusahaan dan Profitabilitas Terhadap Harga Saham - Alpia Aliana (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to analyze the effect of green accounting, company size, and profitability on stock prices of companies in the Energy, Transportation, and Logistics sectors listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. The green accounting variable is measured using the dummy method, company size is proxied by total assets, and profitability is measured using Return on Equity (ROE). The research data is obtained through published financial statements and analyzed using the panel data regression method. The results indicate that green accounting and profitability have a significant positive effect on stock prices, while company size has an insignificant effect. These findings suggest that the implementation of green accounting and profitability levels are important factors considered by investors in making investment decisions.